The 2011 Protests in Inner Mongolia: An Ethno-environmental Perspective. (5th February 2016) - Baranovitch, Nimrod
Abstract: In May 2011, Inner Mongolia experienced the most serious ethnic unrest in the region for 30 years. In this article, I explore the broader context that led to the eruption of the protests, with a particular emphasis on environmental issues. My aim is to explain why environmental issues occupied such a prominent position in the protests, and how these issues were connected to ethnicity. After discussing the material and practical implications of grassland degradation for Mongolian herders, I analyse the symbolic implications of this environmental crisis for the Mongolian educated elite, who have linked environmental issues to ethnic politics and identity. I argue that in the last 20 years or so, Mongolian intellectuals have developed a highly ethnicized environmental discourse, and that this discourse played an important role in informing the 2011 protests. My analysis focuses on this discourse as it is manifested in the domains of art, academia and daily discourse. 摘要: 2011 年 5月内蒙古爆发近 30 年来最严重的民族抗议示威. 本文章分析引发这次骚动的重要原因, 尤其强调生态环境问题的影响. 文章解释环境问题在骚动中为什么占那么重要的位置, 并讨论环境问题和民族问题的关系. 在描述草原退化对蒙古族牧民的物质和实际影响以后, 我的主要焦点就是分析内蒙草原环境危机对蒙古族知识分子的象征性影响. 本文章提出蒙古族知识分子把环境问题, 民族政治和民族身份认同早已结合在一起. 笔者认为, 近 20 年来蒙古族知识分子制造了一种非常民族化的环境话语, 并这个话语在 2011 年的骚动中发挥了很重要的作用.